Thermal risk for common beans due to high temperatures in three counties of Rio Grande do Sul state - Araujo, Guilherme Masarro; Radons, Sidinei Zwick; Engers, Lana Bruna de Oliveira; Knapp, Fábio Miguel; Dapper, Felipe Puff; Moraes, Mariana Poll (Ciência e Natura, 2020)
Common beans are an important protein source for human diet. Much cultivated in small farms it is considered a subsistence crop, employing little cultivation technology. It presents a high susceptibility to temperatures above 28 °C in reproductive periods, causing abortion of plant parts due to the high temperature triggering the plant ethylene synthesis. The agroclimatic zoning for culture does not emphasis on air temperature, which affects the crop. With these assumptions, the aim of this work was to evaluate the high temperature thermal risk for the bean crop in Cruz Alta, Passo Fundo and São Luiz Gonzaga. From the maximum air temperature data obtained since 1961, we obtained the average frequency of days at which the maximum air temperature was equal or greater than 28 °C in ten-day periods. The bigger thermal risk was found in the third ten-day period of January and in the last ten-day period of December. Passo Fundo showed the better thermal conditions for bean crop. São Luiz Gonzaga, even during periods not indicated for the culture, during winter, still showed happen at least one day of thermal risk.